Inflammation in Alzheimer's Disease, and Prevention with Antioxidants and Phenolic Compounds – What Are the Most Promising Candidates? - Sharman, M.; Verdile, Giuseppe; Kirubakaran, S.; Münch, G. (Wiley, 2019)
Early studies of Alzheimer's disease (AD) revealed key neurological features including the deposition of aggregates of insoluble β‐amyloid (Aβ) peptides, the formation of neurofibrillary tangles (NFT), and signs of chronic inflammation. The initial forms of these pathological hallmarks of the disease, including small oligomers of Aβ peptides and the hyperphosphorylated tau which aggregates into NFT, have been assumed to be part of ‘the cause of AD’ and have been specifically targeted to develop an effective monotherapy, but with limited success. In the absence of effective neuroprotective drugs, acetylcholinesterase inhibitors have remained as the drug class that is most used to treat AD, yet they cannot and do not slow the progression of the disease. Imaging studies have confirmed what has long been suspected – that there is a very long pre‐clinical phase, when pathology gradually builds up, possibly starting with chronic inflammation, oxidative stress, and dysregulated metabolism. Emerging therapies are targeted more towards these changes, sometimes as well as the Aβ and NFT pathologies in multi‐targeted approaches, to interfere with the pathological cascades in AD. The aim is to prevent, stop, or at least slow the neurodegeneration before debilitating symptoms appear. This chapter summarises inflammatory and oxidative stress‐related changes that occur in AD, and discusses some emerging therapies and supplements, particularly those directed at inflammation, that may slow pathogenesis of this complex neurodegenerative disease.